The relationship between job characteristics, decent work, and well-being in South Africa's private security sector - Shapiro, Kaylin Lee (Organisational Psychology, 2023)
South Africa's private security sector has become amongst the largest in the world. Research has shown that for the largest category of private security employees - security guards – employment tends to be insecure, wages low, working hours long and few have access to social benefits, such as pay for sick leave, unemployment, retirement, housing, education or family circumstances. This study aimed to investigate if job characteristics should be considered as an aspect relevant for creating decent work for security guards, thus allowing security guards to have a considerable degree of well-being through their work. Specifically, this study asked: Does adding meaningfulness created through a job's content as an indicator of decent work strengthen the relationship among decent work and well-being compared to current decent work indicators? Security guards around South Africa were asked to respond to a questionnaire which assessed job characteristics, decent work, and well-being levels. Analysis of the 98 response sets demonstrated that the job characteristics of security guards appear to have no influence on their perception of decent work nor their well-being, except for task identity which predicted well-being. Managers of private security companies may increase task identity by involving security guards in more aspects of work by enabling them take part in the planning, reporting, and evaluation of projects. This could be including the security guards in meetings with community forums so that they understand crime trends. Future research in the private security sector in South Africa is needed to create awareness of the unfavourable working conditions that many low-level security guards experience and how these can be ameliorated. This would allow private security companies to incorporate socially responsible practices regarding their employees' working conditions which are likely to increase security guards' job productivity at the same time.